Synthesis of the Complexes of S3N3Cl3 with Cadmium(II) and Mercury(II)—Part I - Rani, Shubha; Jadon, S.P.S. (Asian Journal of Chemistry, 2016)
The complexes of S3N3Cl3 with Cd(II) and Hg(II), synthesized and analyzed, are assigned as (S3N3Cl3)4Cd(CH3COO)2 and S3N3Cl3·HgCl2, possessing paramagnetic nature due to 5sp3d and 6sp3 hybridization in subsequent metals and forming quadridentated and bidentated complexes coordinated through Chlorine atom of S3N3Cl3 ring to metal ions.